Lives saved by tuberculosis control and prospects for achieving the 2015 global target for reducing tuberculosis mortality - Philippe Glaziou; Katherine Floyd; Eline L Korenromp; Charalambos Sismanidis; Ana L Bierrenbach; Brian G Williams; Rifat Atun; Mario Raviglione (The World Health Organization, 2011)
OBJECTIVE: To assess whether the global target of halving tuberculosis (TB) mortality between 1990 and 2015 can be achieved and to conduct the first global assessment of the lives saved by the DOTS/Stop TB Strategy of the World Health Organization (WHO). METHODS: Mortality from TB since 1990 was estimated for 213 countries using established methods endorsed by WHO. Mortality trends were estimated separately for people with and without human immunodeficiency virus (HIV) infection in accordance with the International classification of diseases. Lives saved by the DOTS/Stop TB Strategy were estimated with respect to the performance of TB control in 1995, the year that DOTS was introduced. FINDINGS: TB mortality among HIV-negative (HIV-) people fell from 30 to 20 per 100 000 population (36%) between 1990 and 2009 and could be halved by 2015. The overall decline (when including HIV-positive [HIV+] people, who comprise 12% of all TB cases) was 19%. Between 1995 and 2009, 49 million TB patients were treated under the DOTS/Stop TB Strategy. This saved 4.6-6.3 million lives, including those of 0.23-0.28 million children and 1.4-1.7 million women of childbearing age. A further 1 million lives could be saved annually by 2015. CONCLUSION: Improvements in TB care and control since 1995 have greatly reduced TB mortality, saved millions of lives and brought within reach the global target of halving TB deaths by 2015 relative to 1990. Intensified efforts to reduce deaths among HIV+ TB cases are needed, especially in sub-Saharan Africa.